(untitled) (Medical Forum Monthly, 2021)
Objective: To compare the effects of Mulligan Traction Leg Raise versus Slump Stretching on Pain and Functional Disability in Lumbar Radiculopathy. Study Design: Quasi experimental study Place and Duration of Study: This study was conducted at the Family Clinic Baghbanpura, Lahore from September 2020 to February 2021 for a period of six months. Materials and Methods: Consecutive sampling technique was used to select a sample of 40 patients from Physiotherapy department of Family clinic, Lahore. Study was completed in 6 months. Patients randomly allocated into 2 groups. Group A treated with Mulligan Traction leg raise with lumbar stabilization exercises and Group B treated with Slump stretching with lumbar stabilization exercises. Patient evaluated for improvement in symptoms through numeric pain rating scale and oswestry disability index. Each group received treatment session 3 times per week for 4 weeks. Data was analyzed by using SPSS version 21. Results: The result cleared that Group A Mulligan traction leg raise showed significant results in pain and disability with p value less than 0.05. Group A showed decreased in pain with mean value of 1.60±1.536 as compared to Group B which is 4.00±1.947. Where Group A showed improvement in disability with mean value of 16.35±10.038 as compared to Group B where mean value is 45.60±20.849. Group B showed improvement but not showed significant results in comparison of group A. Conclusion: It is concluded that Mulligan traction leg raise with lumbar stabilization exercises is much better technique to improve pain and functional disability in lumbar radiculopathy patients. Slump stretching with lumbar stabilization exercises is also very effective but results showed more significant effects of Mulligan traction leg raise.